Aquaponics System Implementation in Catfish Farming at Labruk Lor Village, Lumajang District, Lumajang Regency - Hertika, Asus Maizar Suryanto; Nurlaelih, Euis Elih; Shofwan, Shofwan; Putra, Renanda Baghaz Dzulhamdani Surya; Alfarisi, Muhammad Asnin (Journal of Innovation and Applied Technology, 2024)
Decreasing water quality and disease outbreaks are negatively affecting catfish farming in Labruk Lor village, Lumajang district, leading to reduced productivity and income for catfish farmers. Service Doctoral Grant programme aims to address issues by offering counselling, training, and optimising yard use through aquaponic activities within the Rumah pangan lestari (RPL) programme. This project is a collaboration between BUMDES Labruk Lor Village, the fish cultivator group "Mina Agung Mandiri" from Labruk Lor village, and the Lumajang Regency Fisheries Service. The methods used in this activity involve socialisation and direct engagement, training and practical application, and monitoring and evaluating. Utilising aquaponics for economic growth can yield the cultivation of 6,984 catfish in 3 m diameter tanks, with an 80% survival rate resulting in a harvest of 6,400 fish weighing 600-700 kg. Vegetables can be harvested 8-10 times per cycle, leading to increased net profit and economic improvement.